O uso da Análise do Comportamento no planejamento e aplicação de uma disciplina de Análise do Comportamento (Brazilian Journal of Behavioral and Cognitive Therapy, 2022)
This work reports the programming, implementation and evaluation of one Behavior Analysis applied to education course for Psychology students. The goal was to undertake a discipline, carried out remotely, using the behavioral principles taught over its own course. The organization of discipline and the main results regarding the students’ performance is presented, along with their evaluation and feedback of the course, and their identification of the behavioral principles involved. It stands out as results the high coincidence between the programmed principles by the teachers and the one identified by the students. Tools are discussed to enable future professionals to act based on behavior analytic principles, while behavior analysts are encouraged to employ these principles themselves in their classroom, in order to both produce meaningful student learning and publicize the relevance and feasibility of the PSI and PCDC in higher education.